Analysis of Exposure to Digital Short Songs (TikTok) on Early Childhood Interest in Traditional Children’s Songs - Serasi Zendrato; Silvia Mariah Handayani (PT. Global Research Collaboration, 2025)
The rapid growth of digital media, particularly short-video platforms such as TikTok, has significantly influenced early childhood music consumption patterns and has the potential to shape children’s musical interests and preferences. This study aims to examine the effect of exposure to digital short songs on TikTok on early childhood interest in traditional children’s songs. A quantitative approach with an explanatory research design was employed. The study involved 25 children aged 4-6 years who were enrolled in Early Childhood Education (PAUD) institutions and selected through purposive sampling. Data were collected using structured questionnaires completed by parents and teachers, measuring the level of exposure to digital short songs and children’s interest in traditional children’s songs. The data were analyzed using descriptive statistics and simple linear regression analysis. The findings reveal that exposure to digital short songs via TikTok has a statistically significant effect on early childhood interest in traditional children’s songs, as indicated by a significance value of 0.046 (p < 0.05). These results suggest that digital media functions as an informal learning environment that can influence children’s musical preferences. However, the impact of digital media exposure largely depends on the quality of content and the presence of appropriate guidance from adults. Therefore, the purposeful and educational use of TikTok may serve as an adaptive strategy to revitalize traditional children’s songs, ensuring their relevance for young learners in the digital era while preserving local cultural values.